A review of antioxidant potential of purple sweet potato (Ipomoea batatas L.): Efficacy of bioactive compound in reducing hypertension / Nur Hanis Jaiman and Nur Rabiatul Adawiah Mohammad Noor - Jaiman, Nur Hanis; Mohammad Noor, Nur Rabiatul Adawiah (2021)
Hypertension is a frequent worldwide health concern and a well-known cardiovascular disease risk factor. This illness is dependent on medicines which can cause a long-term effect. In recent years, purple sweet potato has been employed as an anti-hypertensive agent to prevent cardiovascular disease due to antioxidant activity and anthocyanin content in purple sweet potato. This study determines the efficacy of antioxidant potential in purple sweet potato (Ipomoea batatas L.) in reducing hypertension. Bioactive agents such as phenolic and anthocyanin will act as antioxidants and anti-hypertensive. In particular, the maximum extraction of the total anthocyanin and phenolic contents has been done by the ethanol extraction technique. Antioxidant activity of purple sweet potato was determined by 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity and ferric reducing power activity (FRAP) assay. The findings show that anthocyanins compound in purple sweet potato has a hypotensive effect on lowering systemic blood pressure and malonaldehyde (MDA) levels in the blood. The role of antioxidant activity in purple sweet potato includes regulating the mechanism of imbalance between free radicals, the cycle of oxidative stress in the body and indicative of lipid oxidation or oxidative stress. Consequently, a further study should explore the significance of antioxidant-active chemicals from purple sweet potatoes to promote health benefits in plant-based foodstuffs and promote natural antioxidants.